In vivo Reprogramming of Cancer Metabolism by MYC - Camarda, Roman; Williams, Jeremy; Goga, Andrei (Frontiers in Cell and Developmental Biology, 2017)
The past few decades have welcomed tremendous advancements towards understanding the functional significance of altered metabolism during tumorigenesis. However, many conclusions drawn from studies of cancer cells in a dish (i.e. in vitro) have been put into question as multiple lines of evidence have demonstrated that the metabolism of cells can differ significantly from that of primary tumors (in vivo). This realization, along with the need to identify tissue-specific vulnerabilities of driver oncogenes, has led to an increased focus on oncogene-dependent metabolic programming in vivo. The oncogene c-MYC (MYC) is overexpressed in a wide variety of human cancers, and while its ability to alter cellular metabolism is well established, translating the metabolic requirements and vulnerabilities of MYC-driven cancers to the clinic has been hindered by disparate findings from in vitro and in vivo models. This review will provide an overview of the in vivo strategies, models, mechanisms and conclusions generated thus far by studying MYC’s regulation of metabolism in various cancer models.